Human Immunodeficiency Virus-1 Tat Induces Hyperproliferation and Dysregulation of Renal Glomerular Epithelial Cells - Conaldi, Pier Giulio (American Society for Investigative Pathology, 2002)
Human immunodeficiency virus-associated nephropathy (HIVAN) is etiologically related to the viral infection, but the mechanisms of virus-induced renal injury remain undetermined. Peculiar histopathological features of HIVAN are the enhanced proliferation and the loss of differentiation markers of glomerular epithelial cells (podocytes). We found that podocytes were not permissive to HIV-1 replication. In this study we investigated the effects of the HIV-1 regulatory protein Tat on primary cultures and on a continuous line of podocytes. Our results demonstrated that Tat induced hyperproliferation of these cells in a dose-dependent manner. This activity was primarily mediated by the basic domain of the viral protein. Proteoglycans were required for this phenomenon because Tat-induced increase of podocyte growth was significantly impaired by inhibition of proteoglycan synthesis with β-d-xyloside. In podocyte cultures Tat promoted both the transcription and the release of basic fibroblast growth factor, which contributed to the enhanced cell proliferation. Moreover, Tat deregulated the podocyte phenotype causing down-regulation of maturity markers such as WT-1 and synaptopodin, alteration of cytoarchitecture, and impairment of permselectivity. Together, these results demonstrate that the interaction of extracellular Tat with podocytes can induce alterations that mimic the pathological changes of podocytes detected in HIVAN.